Community Empowerment Through Digital Literacy Education, Entrepreneurship, and Local Economic Governance Based on Community Service Programs - Khairina Eka Setyaputri; Afriansyah Tanjung; Agniya Thahira; Desy Eliana; Devi Wulandari (Ali Institute of Research and Publication, 2026)
The gap in digital literacy capacity, entrepreneurship, and local economic governance remains a structural challenge faced by most Indonesian communities, particularly micro, small, and medium enterprise (MSME) actors, Village-Owned Enterprise (BUMDes) managers, and communities with limited access to quality education. This article aims to describe, analyze, and document the effectiveness of four University-Based Community Service (PBMU) programs implemented by Universitas Muhammadiyah Siber (SiberMU) during the November–December 2025 period. The four programs encompass plant-based entrepreneurship training, BUMDes governance training, digital literacy education on the brain rot phenomenon, and the development of an online Learning Management System (LMS) platform at 4u.mooc.or.id. A descriptive qualitative case study approach was employed, with data collected through pre-tests, post-tests, participatory observation, and participant satisfaction surveys. The results indicate that participants' technical competence in entrepreneurship improved by over 80%, understanding of BUMDes governance was significantly strengthened, digital literacy awareness increased among more than 100 webinar participants, and the LMS platform was successfully launched with eleven free e-courses accessible to the wider public. The study concludes that a multidisciplinary, online, and outcome-oriented community service approach can produce measurable transformative impacts on target groups, and recommends strengthening post-program mentoring mechanisms and multi-stakeholder collaboration to sustain long-term program outcomes.